Orbeez. Issue 6 (June 2015) - Darracq, Michael A.; Cullen, Jennifer; Rentmeester, Landen; Cantrell, F. Lee; Ly, Binh T.
<x xml:space="preserve">Abstract</x> Objectives In December 2012, the U.S. Consumer Product Safety Commission recalled the water-absorbing toy WaterBalz after reports of small intestine obstruction after ingestion by children. Orbeez, another water-absorbing bead, remains available and is marketed as a children's toy. We sought to determine the extent to which Orbeez enlarge in various liquid media and the potential risk for bowel obstruction. Methods Three Orbeez beads were added to 210 mL of the following liquid media: room temperature tap water, whole milk, simulated gastric fluid, GoLytely (polyethelyelene glycol, 3350 and electrolytes), and vodka (40% ethanol by volume). Diameters before exposure to media were measured using a caliper to the nearest 0.1 mm and again at 1, 2, 4, 6, 12, and 24 hours. Ten beads were then added to the beads already immersed in simulated gastric fluid and water and observed for an additional 72 hours (96 hours total) for clumping or increase in diameter. Clumping was defined as two or more beads remaining persistently adherent to one another despite gentle circular movement (swirling) of the liquid. Results Growth in each of the media was observed. Growth in simulated gastric fluid was minimal, whereas the beads were observed to be the largest after 24 hours in vodka. Clumping of the beads was not observed to occur. Conclusions Orbeez beads enlarge to a different extent in different liquid media. It is unlikely that Orbeez beads would expand to sizes or demonstrate clumping that would be concerning for intestinal obstruction.